2020
DOI: 10.14715/cmb/2020.66.4.5
|View full text |Cite
|
Sign up to set email alerts
|

p-Cymene metallo-derivatives: An overview on anticancer activity

Abstract: Metallo-drugs have gained a huge attention among scientific community in the couple years. These drugs types have become important compounds in cancer therapy, where, for instance, platinum complexes are being used against many tumors worldwide. Nonetheless, to p-cymene metallo-derivatives a promising anticancer potential has also been increasingly proposed. In this sense, the present review aims to provide an in-depth revision of p-cymene metallo-drugs possible mechanisms of anticancer action for upcoming pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Sixty compounds were detected in the aqueous extract of H. parva via GC-MS analysis ( Supplementary Material, Figure S2 and Table S1 ). As it was shown in Table S1 , there were two molecules, including methyl ester octadecanoic acid [ 24 , 25 , 26 ] and 1-methyl-4-(1-methyl phenyl)-benzene [ 27 , 28 , 29 ] that have been proved to have proliferative biological activity. Other biological activities were also observed in other molecules of aqueous extract of H. parva , including anti-oxidant, anti-microbial, anti-inflammatory, etc.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixty compounds were detected in the aqueous extract of H. parva via GC-MS analysis ( Supplementary Material, Figure S2 and Table S1 ). As it was shown in Table S1 , there were two molecules, including methyl ester octadecanoic acid [ 24 , 25 , 26 ] and 1-methyl-4-(1-methyl phenyl)-benzene [ 27 , 28 , 29 ] that have been proved to have proliferative biological activity. Other biological activities were also observed in other molecules of aqueous extract of H. parva , including anti-oxidant, anti-microbial, anti-inflammatory, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Sixty compounds were detected in the aqueous extract of H. parva via GC-MS analysis (Supplementary Material, Figure S2 and Table S1). As it was shown in Table S1, there were two molecules, including methyl ester octadecanoic acid [24][25][26] and 1-methyl-4-(1-methyl phenyl)-benzene [27][28][29] that have been proved to have proliferative biological activity.…”
Section: Gas Chromatography-mass Spectrometry (Gc-ms) Analysis Detect...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the molecules in the aqueous extract from H. parva had different biological effects. As it was shown in Table 1, there were two molecules including methyl ester octadecanoic acid (24-26) and 1-methyl-4-(1-methylethenyl)-benzene (27)(28)(29) which has been proved to have proliferative biological activity. Other biological activities were also observed in other molecules of aqueous extract of H. parva including anti-oxidant, anti-microbial, anti-in ammatory, etc.…”
Section: Gc-ms Analysis Detected Proliferative Compounds In the Aqueo...mentioning
confidence: 99%